Порівняльний аналіз алгоритмів оптимальної фільтрації за точністю отримання навігаційного рішення - Раєвський, М.В. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
A comparative analysis of the classical Kalman filter algorithm and one of its modification (modification of Andrews) is held. The aim of analysis is the information to be obtained about both algorithms of linear systems optimal estimation in the plane of navigation solution accuracy.